Current impulse response of thin InP p+–i–n+ diodes - YOU, A; CHEANG, P (ELSEVIER SCI LTD, 2006)
The simulation of current impulse response using random response time model in avalanche photodiode (APD) is presented. A random response time model considers the randomness of times at which the primary and secondary carriers are generated in multiplication region. The dead-space effect is included in our model to demonstrate the impact on current impulse response of thin APDs. Current impulse response of homojunction InP p(+)-i-n(+) diodes with the multiplication widths of 0.1 and 0.2 mu m are calculated. Our results show that dead-space gives a slower decay rate of current impulse response in thin APD, which may degrade the bit-error-rate of the optical communication systems. (c) 2006 Elsevier Ltd. All rights reserved.